Exploiting polarity and chirality to probe the Hsp90 C-terminus. Issue 12 (23rd July 2018) - Forsberg, Leah K.; Davis, Rachel E.; Wimalasena, Virangika K.; Blagg, Brian S.J.
Graphical abstract: Abstract: Inhibition of the Hsp90 C-terminus is an attractive therapeutic approach for the treatment of cancer. Novobiocin, the first Hsp90 C-terminal inhibitor identified, contains a synthetically complex noviose sugar that has limited the generation of structure-activity relationships for this region of the molecule. The work described herein utilizes various ring systems as noviose surrogates to explore the size and nature of the surrounding binding pocket.